Kriminalitas dan Hukum: Perspektif Sosiologi Terkait Kontrol Sosial dan Hukum - Maulida, Kartika (Jurnal Hukum Caraka Justitia, 2025)
This article discusses the relationship between criminality and law from a sociological perspective, focusing on social control and the role of law in regulating societal behavior. Criminality is often understood as a violation of prevailing legal norms, but sociology views it as a social phenomenon influenced by various factors, including social, economic, and cultural structures. In this context, the law functions as a tool of social control aimed at maintaining order and stability. The article explores how social norms are codified into law and how the law interacts with power dynamics and group interests within society. This approach emphasizes the importance of understanding the social context in the application of law and the effectiveness of social control in addressing criminality. Through theoretical analysis and literature review, the article offers a more comprehensive understanding of the relationship between crime and law in modern social structures.